Automated Attenuation Based Tube Potential Selection of the Lower Extremity Runoff: A Comparison to Fixed Kilovolt with Automated Tube Current Modulation. Issue 5 (September 2017) - Beeres, Martin; Juhee, Kang; Bucher, Andreas M.; Frellesen, Claudia; Albrecht, Moritz; Wichmann, Julian L.; Park, Clara; Kaup, Moritz; Scholtz, Jan Erik; Vogl, Thomas J.; Gruber-Rouh, Tatjana; Bodelle, Boris
Abstract : Purpose: The aim of this study was to evaluate the impact of automated attenuation-based tube potential selection (ATPS) on image quality and radiation dose exposure parameters at a computed tomography angiography (CTA) lower-extremity runoff. Materials and Methods: Two hundred forty patients (156 men, 84 women) underwent CTA examinations of the lower-extremity runoff on a second-generation dual-source computed tomography system: 120 patients at a fixed tube potential of 120 kV and a tube current of 180 reference mAs, another 120 patients using automated ATPS. Volume computed tomography dose index (CTDIvol), dose-length-product (DLP), body diameters, noise, signal-to-noise ratio, and subjective image quality were compared. Results: In the ATPS group, 80 kV was automatically selected in 102 patients, 100 kV in 15 patients, and 120 kV in 3 patients; 140 kV was not chosen in any of the cases. The median CTDIvol of 4.81 mGy (2.2–10.6 mGy) and DLP of 568 mGy⋅cm (203–1324 mGy⋅cm) in the ATPS group were significantly lower compared with the CTDIvol of 8.1 mGy (4.4–14.4 mGy) and DLP of 1027.5 mGy⋅cm (509–1806 mGy⋅cm) in the fixed 120-kV group ( P < 0.01). Image quality was comparable ( P > 0.05). Conclusion: Automated ATPS allows for significant dose savings in lower-extremity runoff CTA, whereas image quality remains constant at a high level.